Dukungan Spiritual Dengan Tingkat Stres Pada Narapidana di Lembaga Pemasyarakatan Kelas II A Bulukumba - Nurlina; Haerati (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2020)
Stress is a physical and psychological reaction to any demands that cause tension and disturb the stability of everyday life. Most people experiencing stress are prisoners. The number of fostered residents in South Sulawesi Province in 2018 was 10,286 including 336 fostered residents in Lapas Bulukumba. If this stress lasts a long time, it can have an impact on one's body. Therefore, prevention efforts to deal with stress, are given spiritual support. This study aims to determine the relationship between spiritual support and stress levels in prisoners with drug cases in Class II A Penitentiary in Bulukumba in 2019. The method of research is using research analytic, with design cross-sectional. The population in this study is prisoners with drug cases. The samples in the study have amounted to 47 respondents with the technique of taking samples using methods of Consecutive sampling. Retrieval of data is done by using a sheet questionnaire on the support of the spiritual and the DASS 42 ( Depression Anxiety and Stress Scale 42 ). Analysis of the data used by using the Chi-Square test. In research, it obtained results that support spiritual support to the category of less stress over lots of 21 respondents (87.5%) compared with the stress of three respondents (12.5%). While the support of spirituality does not support the category of stress as much as 23 respondents (100%). Based on the analysis that has been done by using test Chi-Square, the obtained value p-value = 0.000 (p < 0.05 ). There is a relationship of support spiritual with the level of stress on inmates at the Institute of Corrections Class II A Bulukumba. It is recommended to prison staff and health workers in prison to always pay attention to the mental health conditions of inmates. It is expected also on the respondents to increase the spiritual by way of multiplying follow the activities of the religious.